Personalised Anaesthesia, Arterial Blood Gases and Tissue Hypoxia: Modulating Postoperative Regeneration and Healing - Jayaram, Jacynta; Baig, Atif Amin; Thunder Oo, Aey; Mynt Hoo, Phone; Win Kyaw, Zaw; Hla Hla Thein, Khin; Chopra, Shivani; Sunil, Junapudi; Chopra, Hitesh (Scripta Medica, 2026)
The fundamental limiting factor of major surgery is the body's ability to regenerate and heal tissue after it has been operated on, but this process must take its own course. Recent evidence is available to show that the method of anaesthesia employed during operative procedures and in particular the maintenance of arterial blood gases (ABG), may have a significant influence on regenerative processes by altering, as the case may be, the degree of hypoxia present within tissues. This narrative review addresses the issue of an individualised plan of anaesthesia, aiming to maintain a constant and progressive improvement in oxygen tension (PaO2) and carbon dioxide tension (PaCO2), as well as their impact on cellular repair processes. The view taken is that the best results cannot be attained by a rigid generalised state of normoxia, but by individualising the treatment by the means of the arterial blood gas results to achieve ends which will have a bearing upon such factors as hypoxia-inducible factor 1-alpha (HIF1α), which refers to a factor evidenced in the regulation of angiogenesis, collagen synthesis and the processes of wound healing. We are considering important clinical experiments and data, taking into account oxygenation strategies, ventilation policies and methods of checking that support individual arterial blood gas aims with the goal of improving the quality of recovery and outcomes beyond the operative phases.
Keywords: Precision medicine; Anaesthesia; Postoperative period; Early goal-directed therapy